2006
DOI: 10.4049/jimmunol.177.1.459
|View full text |Cite
|
Sign up to set email alerts
|

PneumocystisCell Wall β-Glucans Induce Dendritic Cell Costimulatory Molecule Expression and Inflammatory Activation through a Fas-Fas Ligand Mechanism

Abstract: Respiratory failure during Pneumocystis pneumonia is mainly a consequence of exaggerated inflammatory responses to the organism. Dendritic cells (DCs) are the most potent APCs in the lung and are key to the regulation of innate and adaptive immune responses. However, their participation in the inflammatory response directed against Pneumocystis infection has not been fully elucidated. Therefore, we studied the role of Pneumocystis carinii, as well as Saccharomyces cerevisiae, cell wall-derived β-glucans, in DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 37 publications
2
69
2
Order By: Relevance
“…We previously showed that human DCs stimulated with PCBG are potent inducers of some features of the Th1 phenotype, in the absence of IL-12 (31). The lack of the p35 subunit, rather than the abundant p40 subunit, was determined to be the main reason for deficiency of total IL-12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that human DCs stimulated with PCBG are potent inducers of some features of the Th1 phenotype, in the absence of IL-12 (31). The lack of the p35 subunit, rather than the abundant p40 subunit, was determined to be the main reason for deficiency of total IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that human DCs stimulated with PCBG are potent inducers of a Th1 phenotype in the absence of IL-12 (31). Over the last several years, Th17 cells have been described as important components necessary for the clearance of fungal infections, including Pneumocystis pneumonia (19)(20)(21).…”
Section: Pcbg Induce Activation Of the Human Il-23/il-17 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…The Sophy β-glucan-induced sFas production by cultured PBMCs or U937 cells observed in this study suggests that Sophy β-glucan might prevent apoptosis by suppressing the Fas/FasL apoptosis induction system, and that Sophy β-glucan might be used to examine the role of apoptosis in the maintenance of homeostasis. For example, it was recently reported that the β-glucans contained within the cell wall of Pneumocystis induced costimulatory molecular expression in dendritic cells (DCs) and inflammatory activation mediated by the Fas/FasL apoptosis induction system (6). If Sophy β-glucan-induced sFas production by PBMCs can prevent the onset of apoptosis regulated by the Fas/FasL system, then Sophy β-glucan may have the potential ability to downregulate inflammatory responses.…”
Section: Immunological Actions Of Sophy β-Glucanmentioning
confidence: 99%
“…It is considered that by enabling DC maturation and activation, β-glucan activates cytokine response, and so it is considered to effect the regulation of immune response [19]. Kikuchi et al have also reported that Candida β-glucan may augment DC maturation [15].…”
Section: Discussionmentioning
confidence: 99%